2020
DOI: 10.5430/wje.v10n4p160
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Knowledge of Special Educational Needs and Disability Students and Their Classroom Management Approaches

Abstract: Parents and many other stakeholders usually complain about equity and inclusivity of students with special educational needs (SEN) in the mainstream schools. The purpose of the study was to find out the level of teachers’ knowledge of special educational needs and disability students and their classroom management procedures and strategies. The study adopted qualitative paradigm and a descriptive approach to gather data and were thematically analysed. The findings showed that teachers’ knowledge of special edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Some students struggle with a variety of disabilities and learning problems. As Gyasi et al, (2020) point out, SEN is used to students who, in comparison to children of the same age group, have learning difficulties that make it challenging for them to learn. This means that investigating SEN issues refers to assessing, diagnosing, developing instructional programs, and appropriate teaching/learning strategies as well.…”
Section: Students With Special Educational Needs (Sen)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some students struggle with a variety of disabilities and learning problems. As Gyasi et al, (2020) point out, SEN is used to students who, in comparison to children of the same age group, have learning difficulties that make it challenging for them to learn. This means that investigating SEN issues refers to assessing, diagnosing, developing instructional programs, and appropriate teaching/learning strategies as well.…”
Section: Students With Special Educational Needs (Sen)mentioning
confidence: 99%
“…In the nineteenth century, children with mental problems were included. The emphasis of teachers at the time was on the need for help to make life meaningful for SEN, students (Alkahtani, 2016;Gyasi et al, 2020). According to Padurean (2014), students with SEN find it difficult to adapt to a hostile setting where they are made fun of, learning requires a lot of work, and teachers are not fully prepared to manage these circumstances and provide the children with the greatest educational assistance.…”
Section: Introductionmentioning
confidence: 99%
“…They estimated that they had satisfactory knowledge about learning difficulties, struggling learners, speech-language disorders, ADHD, and intellectual disabilities, while they had poor one about autism, blindness, cerebral palsy, deafness, mental illness, and traumatic brain damage. Research shows that teachers have limited knowledge about children with special educational needs (Gyasi, Okrah, and Anku, 2020) or limited knowledge about how to treat and teach this population in the regular classroom (Mensah, Gyamfi, and Agbezudor, 2022). The focus of this paper is the examination of the information level of educational workers about Down syndrome, and the analysis of previous research has shown that very little research has dealt with this issue.…”
Section: Introductionmentioning
confidence: 99%
“…If teachers are to be competent in educating children with special learning requirements, it is critical that they possess the relevant and necessary training (Gyasi, Okrah, & Anku, 2020). Teachers' inability to assist learners with special academic requirements as a result of insufficient equipment may result in learning deficits for such students.…”
Section: Inadequate Teacher Development and Supportmentioning
confidence: 99%
“…In sum, the appropriate preparation of teachers is essential to capacitate teachers to exploit learners' potential especially in special educational needs [SEN] (Gyasi, Okrah, & Anku, 2020). Teachers' inability to assist students with special demands as a result of insufficient preparation and support might result in learning hurdles being experienced by these students.…”
Section: Staff With Inclusion Expertisementioning
confidence: 99%